Agile Management Implementation and Organizational Performance Enhancement in Post-Pandemic Era - Steviani Batti; A.M. Fadli Mappisabbi; Nurasia Natsir (Pusat Riset dan Inovasi Nasional, 2025)
The COVID-19 pandemic has fundamentally transformed organizational management paradigms, accelerating the adoption of agile methodologies beyond traditional software development contexts. This comprehensive study examines the impact of agile management implementation on organizational performance in Indonesian technology companies during the post-pandemic recovery period. Through a quantitative cross-sectional analysis involving 150 technology companies across Indonesia from January 2023 to August 2024, this research employed validated questionnaires measuring agile implementation maturity and organizational performance indicators. Structural Equation Modeling (SEM) was utilized to analyze causal relationships between agile practices and performance outcomes.